Consonantal Variation of Hindi-Urdu Loanwords in Standard English: A Phonological Analysis - Bairam Khan; Mohammad Asad; Mahboob Zahid (WISE Pendidikan Indonesia, 2024)
This study explores the complex phonological transformations involved in adapting Hindi-Urdu loanwords into Standard English. Examining a corpus of approximately 300 loanwords, this research identifies systematic phonological changessuch as deaspiration, devoicing, deretroflexion, and deuvularizationthat align these borrowed words with English phonotactic norms. For instance, Hindi-Urdu aspirated sounds typically lose aspiration in English, while retroflex consonants shift to alveolar positions, reflecting the structural requirements of English phonology. These transformations underscore the adaptability of Hindi-Urdu phonemes in response to English phonetic constraints, facilitating smoother integration into the English sound system. Additionally, deviations from expected patterns, or “misiterations,”reveal the influence of perceptual and sociolinguistic factors that add complexity to the adaptation process. By focusing on consonantal changes specifically, this study fills a gap in the literature on phonological adaptation in cross-linguistic contexts, particularly between Indo-Aryan and Germaniclanguages. The findings provide a detailed view of consonantaladjustmentsthat occur in loanwords, enhancing our understanding of language contact dynamics. This research also suggests new interdisciplinary avenues for exploring phonological adaptation by incorporating cognitive and sociolinguistic perspectives to further analyze the complexities of loanword integration.